Creatures Bound for Glory: Biotechnological Enhancement and Visions of Human Flourishing. (May 2019) - Burdett, Michael; Lorrimar, Victoria
The human enhancement debate is fundamentally based on divergent ideals of human flourishing. Using the complementary, though often contrasting, foci of creaturehood and deification as fundamental to the good life, we examine these visions of human flourishing inherent in transhumanist, secular humanist and critical posthumanist positions on human enhancement. We argue that the theological anthropologies that respond to human enhancement and these other ideologies tend to emphasise either creaturehood or deification to the neglect or detriment of the other. We propose in response that understanding humans as creatures bound for glory integrates both dimensions of the human being into the one grand vision of flourishing God has for humanity.